Contemporary impacts of a cancer diagnosis on survival following in-hospital cardiac arrest. (September 2019) - Guha, Avirup; Buck, Benjamin; Biersmith, Michael; Arora, Sameer; Yildiz, Vedat; Wei, Lai; Awan, Farrukh; Woyach, Jennifer; Lopez-Mattei, Juan; Plana-Gomez, Juan Carlos; Oliveira, Guilherme H.; Fradley, Michael G.; et al.
Abstract: Aim: The objective of this study was to determine whether survival and post-arrest procedural utilization following in-hospital cardiac arrest (IHCA) differ in patients with and without comorbid cancer. Methods: We retrospectively reviewed all adult (age ≥18 years old) hospital admissions complicated by IHCA from 2003 to 2014 using the National Inpatient Sample (NIS) dataset. Utilizing propensity score matching using age, gender, race, insurance, all hospital level variables, HCUP mortality score, diabetes, hypertension and cardiopulmonary resuscitation use, rates of survival to hospital discharge and post-arrest procedural utilization were compared. Results: From 2003 to 2014, there were a total of 1, 893, 768 hospitalizations complicated by IHCA, of which 112, 926 occurred in patients with history of cancer. In a propensity matched cohort from 2012 to 2014, those with cancer were less likely to survive the hospitalization (31% vs. 46%, p < 0.0001). Following an IHCA, rates of procedural utilization in patients with cancer were significantly less when compared to those without a concurrent malignancy: coronary angiography (4.0% vs. 13.0%), percutaneous coronary intervention (2.2% and 8.0%), targeted temperature management (0.8% vs. 6.0%); p < 0.0001 for all comparisons. This patient population was less likely to have acute coronary syndrome (12.6% vs. 27.0%) or congestive heart failure (24.5% vs. 38.2%); p < 0.0001 for both comparisons. Survival improved in both groups over the study period (p < 0.0001). Conclusions: Patients with a history of cancer who sustain IHCA are less likely to receive post-arrest procedures and survive to hospital discharge. Given the expected rise in the rates of cancer survivorship, these findings highlight the need for broader application of potentially life-saving interventions to lower risk cancer patients who have sustained a cardiac arrest.